2022
DOI: 10.1108/tr-11-2021-0497
|View full text |Cite
|
Sign up to set email alerts
|

Travel app shopping on smartphones: understanding the success factors influencing in-app travel purchase intentions

Abstract: Purpose With the diffusion of innovation theory (DOI) and theory of planned behaviour (TPB) as the guiding theoretical perspectives, this research aims to identify the factors motivating user attitudes and in-app purchase intentions (IAPIs). The moderating impact of user inertia towards TPB constructs was also explored. Design/methodology/approach A total of 500 responses were received via an online survey fielded from July to October 2021. The data were then analysed using partial least square structural eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 58 publications
3
31
0
Order By: Relevance
“…An MTA with augmented reality (AR) features can potentially enhance travel experiences by providing location-based services (LBS) using GPS and information to tourists based on their current location (Chen and Tsai, 2017). The perceived relative advantages, which included location-based recommendations, simpler booking under one platform and customised services, positively influenced user attitudes towards app-based travel shopping on smartphones (Lim et al , 2022).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…An MTA with augmented reality (AR) features can potentially enhance travel experiences by providing location-based services (LBS) using GPS and information to tourists based on their current location (Chen and Tsai, 2017). The perceived relative advantages, which included location-based recommendations, simpler booking under one platform and customised services, positively influenced user attitudes towards app-based travel shopping on smartphones (Lim et al , 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The theoretical basis for this study involved one-stop solution characteristics and emerging MTA smart features. The MTA that includes all aspects of a trip in a one-stop solution is a key to enhance the travel experience (Lim et al , 2022). Instead of making multiple bookings through various websites, the traveller should be able to complete all travel-related bookings on one platform (Gomes et al , 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consumer preference and overall evaluation of a product will be greatly influenced by their attitude towards the product. Past research showed that attitude is significantly associated to PI (Abbasi et al, 2021;Qi and Ploeger, 2021;Dionysis et al, 2022;Lim et al, 2022;Sousa et al, 2022;Roh et al, 2022). Specific to the context of SE, the study by Lee et al (2021) on consumer PI on Malaysian SE products revealed a positive correlation between attitude and PI.…”
Section: Attitudementioning
confidence: 90%
“…Many researchers have reported an association between PBC and PI (Abbasi et al, 2021;Qi and Ploeger, 2021;Dionysis et al, 2022;Lim et al, 2022;Sousa et al, 2022). Thus, it is proposed that H3.…”
Section: Subjective Normsmentioning
confidence: 98%